2014
DOI: 10.1097/mao.0000000000000313
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Hearing Loss and Dementia

Abstract: Objective To determine whether baseline hearing loss increases cognitive decline and risk for all-cause dementia in a population of elderly individuals. Study design Longitudinal cohort study Setting Community-based, outpatient Patients Men and women aged 65 years or older without dementia at baseline Intervention(s) All subjects completed the Modified Mini-Mental Status Exam (3MS-R) at baseline and over 3 triennial follow-up visits. Hearing loss (HL) at baseline was based on observation of hearing dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
147
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 314 publications
(156 citation statements)
references
References 45 publications
5
147
0
4
Order By: Relevance
“…Our results support recent population-based longitudinal studies that demonstrated older persons with HL were more likely to experience accelerated cognitive decline or incident dementia [5,6,7,8]. There is little previous literature investigating the association of HL with MCI, a prodromal stage of dementia that confers a high risk of developing dementia.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Our results support recent population-based longitudinal studies that demonstrated older persons with HL were more likely to experience accelerated cognitive decline or incident dementia [5,6,7,8]. There is little previous literature investigating the association of HL with MCI, a prodromal stage of dementia that confers a high risk of developing dementia.…”
Section: Discussionsupporting
confidence: 80%
“…The use of hearing tests such as the pure tone audiogram is difficult in large population studies due to the time required, cost, and subject compliance. Population studies have variously used other methods to report the presence of HL including self-report, difficulty in hearing cognition tests, requirement for an audio amplifier to complete cognition tests, and hearing aid use [7]. We used the whispered voice test as it is a simple hearing test and one of the most accurate available compared to pure tone audiometry, with a reported sensitivity of 72.3% and specificity of 70% in detecting HL of ≥40 dB in the better hearing ear in the local elderly Singaporean population [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study built on previous longitudinal studies conducted in the United States and Wales that found that individuals with moderate and severe hearing loss were at greater risk of developing dementia 6, 7, 12, 22. Six hundred thirty‐nine adults aged 65 and older from the Baltimore Longitudinal Study of Aging were prospectively analysed over 11.9 years 7.…”
Section: Discussionmentioning
confidence: 99%
“…Projections in both the US and UK suggest that the number of people affected by ARHL will effectively double by 2031, largely due to an increased lifespan [2] (Action on Hearing Loss http://www.action onhearingloss.org.uk/your-hearing/about-deafness-and-hearing-loss/statistics.aspx). ARHL inevitably causes communication difficulties and is associated with social isolation, depression and reduced physical and cognitive function [3,4]. There is a growing literature on the association between hearing loss and cognitive decline; however, it is unknown whether this link is via common pathological mechanisms or because the lack of auditory input contributes to accelerated cognitive decline [5].…”
Section: Introductionmentioning
confidence: 99%